Penerapan Media Pembelajaran Tiga Dimensi untuk Meningkatkan Hasil Belajar Kognitif Peserta Didik pada Materi Sistem Tata Surya - Erwin Umbu Dangu Ela; Yohana Makaborang (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
This study aims to: 1) describe the application of three-dimensional learning media to students' cognitive learning outcomes; and 2) describing the increase in cognitive learning outcomes of Class VII students of SMP Negeri 4 Umbu Ratu Nggay, Pahomba Village, Umbu Ratu Nggay District, Central Sumba Regency, East Nusa Tenggara Province after using three-dimensional learning media on solar system material. This type of research is Classroom Action Research (CAR), which is conducted in two cycles. Each cycle consists of planning, implementation, action, evaluation, and reflection stages. The subjects of this study were class VII students of SMP Negeri 4 Umbu Ratu Nggay for the 2021/2022 academic year, which consisted of 12 students. The data obtained in this study are in the form of students' cognitive learning outcomes taken from the application of the three-dimensional media learning method. The instruments used are interview sheets, tests, and documentation. The results of the research and data analysis in cycle I and cycle II revealed that there was an increase in the cognitive learning outcomes of class VII students of SMP Negeri 4 Umbu Ratu Nggay. This is indicated by an increase in the percentage of students' cognitive learning outcomes in science lessons on the solar system material. The percentage of the pre-test score in the first cycle category was 25% complete and 75% incomplete, and the post-test value in cycle I increased, namely the complete category was 41% and 59% incomplete. In cycle II there was an increase where the percentage of the pre-test score with the complete category was 66.6% and 33.4% incomplete, and the post-test value in the second cycle category was 91.3 complete and 8.3% incomplete.